Opposition in transition: pre-electoral coalitions and the 2018 electoral breakthrough in Malaysia. Issue 2 (17th February 2020) - Ufen, Andreas
ABSTRACT: In May 2018, the Malaysian opposition coalition Pakatan Harapan or Hope Alliance won the federal elections for the first time in the history of the country. The electoral authoritarian system is now in a state of transition. The electoral breakthrough was the result of longer-term socio-economic transformations, but the formation of a strong pre-electoral coalition was ultimately decisive for the victory. The article compares various coalitions and their performance during seven elections since 1990. The structured, focused comparison analyses the coalitions during this period because prior to 1990 the opposition was fragmented. On the basis of a three-level concept regarding the strength of pre-electoral coalitions, the article argues that Pakatan Harapan was successful because the coalition was sufficiently comprehensive (as indicated by the number and the competitiveness of candidates), cohesive (concerning ideological proximity and behavioural routinization) and well-rooted in society (in terms of linkages to voters/supporters and to civil society networks or organizations).